Novel allosteric covalent inhibitors of bifunctional Cryptosporidium hominis TS-DHFR from parasitic protozoa identified by virtual screening. Issue 11 (1st June 2019) - Ruiz, Victor; Czyzyk, Daniel J.; Valhondo, Margarita; Jorgensen, William L.; Anderson, Karen S.
Graphical abstract: Abstract: Protozoans of the genus Cryptosporidium are the causative agent of the gastrointestinal disease, cryptosporidiosis, which can be fatal in immunocompromised individuals. Cryptosporidium hominis ( C. hominis ) bifunctional thymidylate synthase-dihydrofolate reductase (TS-DHFR) is an essential enzyme in the folate biosynthesis pathway and a molecular target for inhibitor design. Previous studies have demonstrated the importance of the Ch TS-DHFR linker region "crossover helix" to the enzymatic activity and stability of the Ch DHFR domain. We conducted a virtual screen of a novel non-active site pocket located at the interface of the Ch DHFR domain and crossover helix. From this screen we have identified and characterized a noncompetitive inhibitor, compound15, a substituted diphenyl thiourea. Through subsequent structure activity relationship studies, we have identified a time-dependent inhibitor lead, compound15D17, a thiol-substituted 2-hydroxy- N -phenylbenzamide, which is selective for Ch TS-DHFR, and whose effects appear to be mediated by covalent bond formation with a non-catalytic cysteine residue adjacent to the non-active site pocket.